Constitutive and induced carotenoid production from intact plant and in vitro cultures of selected medicinal plants - Fatimah Azzahra binti Mohd Zaifuddin (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2014)
Ulam or traditional vegetables and medicinal plant species in Malaysia comprise of more than 120 species representing various families ranging from groundcovers, shrubs to trees. The leaves, shoots, flowers, fruits, roots and rhizomes of the vegetables are cooked or eaten fresh as salads and are consumed to add variety and flavour to the diet, as well as for their health benefits. These species are rich in carbohydrate, protein, mineral and vitamins. This study is aimed at establishing an analytical method of carotenoid analysis in a wide range of ulam and medicinal plants as well as exploring the diversification of dietary carotenoids and their respective compositions and concentrations, thus providing basic knowledge for carotenoid biogenesis or their regulatory mechanism through an in vitro model system for future enrichment and enhancement. It was found that ulam species differ greatly with respect to types and concentrations of carotenoids in leaves. A total of 28 species were evaluated for quantitative and qualitative carotenoid composition through high performance liquid chromatography (HPLC) analysis. The main carotenoids identified in these selected ulam were neoxanthin, violaxanthin, lutein, zeaxanthin, β-cryptoxanthin, α-carotene and β-carotene. The ratio of these carotenoids varied between species. Interestingly, these carotenoid profiles were also found in varying concentration and composition in different species. Total carotenoid content quantified in all of the samples lies between 1.31 ± 0.01 to 190.30 ± 3.43 milligram/gram dry weight (mg/g DW) where Sauropus androgynus has the highest content. Neoxanthin was detected in 12 species (6.87 ± 0.76 to 142.40 ± 3.57 mg/g DW); violaxanthin in 10 species (1.87 ± 0.09 to 28.06 ± 0.65 mg/g DW), zeaxanthin in only five species (45.74 ± 2.32 to 123.45 ± 12.3 mg/g DW), β-cryptoxanthin in seven species (0.04 ± 0.00 to 0.07 ± 0.00 mg/g DW) and α-carotene in 12 species (0.38 ± 0.03 to 5.04 ± 0.25 mg/g DW). Meanwhile, lutein and β-carotene were found in most of the species but their concentrations varied from 0.72 ± 0.00 to 16.53 ± 0.97 mg/g DW and 0.54 ± 0.02 to 3.09 ± 0.06 mg/g DW, respectively. The total vitamin A activity (in terms of retinol equivalent, RE) of every species is also included in this study. The results suggested that at least 21 of the ulam and medicinal species may be used as alternative food intervention to eliminate vitamin A deficiency (VAD) as a public health concern. Apart from that, this study also established a schematic workflow to produce an α-carotene standard (with about 95-97% purity) from one of the selected ulam and medicinal plant species, namely Morinda citrifolia (mengkudu). Production of the α-carotene standard is essential to support the food carotenoid analysis since this standard has limited availability in the commercial market and it is difficult to maintain the pure ones. Through the first part of this study, the variation of carotenoid content observed in one plant species from others has provided indications that metabolic flux along the carotenoid biosynthetic pathway might be regulated by several factors. Although the biosynthetic pathway has been well elucidated over the past decades, the knowledge on how this pathway is regulated remains poorly understood. With this in mind, plant in vitro cultures were used as model systems to study regulatory mechanisms of carotenogenesis in three selected species (Ruta angustifolia, M. citrifolia and Ocimum basilicum). The results suggest that a regulatory step for the carotenoid biosynthetic pathway versus environmental stress is mediated by abscisic acid (ABA) and involves the epoxidation of zeaxanthin to violaxanthin by zeaxanthin epoxidase during the first committed step in ABA biosynthesis. Zeaxanthin appears to be the key factor and indicator for the presence of environmental stress. Not surprisingly, the response to such environments appeared to be